Commodification Digital Comics on Instagram Account @asupankomik_ - Rafi’i; Khairul Syafuddin (PT Inovasi Pratama Internasional, 2023)
Instagram is one of the social media that is used to disseminate information widely. The social media has power in its visual text. One account that uses Instagram is @asupankomik_. The account uses Instagram not to upload personal content. However, to reupload works from other comic creators. This study aims to determine the commodification of text by the @asupankomik_ account in order to gain profit. The method used in this research is qualitative. The unit of analysis in this study is content from the @asupankomik_ account. The analysis technique used is semiotic analysis from Charles S. Pierce. The results of this study found that the content chosen by these accounts tends to describe the life of the middle and lower social classes. This can lead to stereotypes about their lives. In addition, the commodification carried out by @asupankomik_ changed the use value of comics as entertainment content into content for economic gain. The benefits are not only in the form of money. But also in the form of investment in the form of the number of followers and posts.